2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.419
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Presence on Individual Phishing Victimization

Abstract: Research on phishing has implicated users' heuristic processing as the reason why they fail to recognize deception cues and fall prey to phishing attacks. Other research on online behavior has found that the attributes of the medium activate heuristics that contribute to feelings of presence and enhance the persuasiveness of presented information. The deception literature has, however, yet to examine how such medium attributes lead to victimization in a phishing attack. The present research thus fills an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…They found that attention to visceral triggers and phishing detection indicators and to users' phishing knowledge played a critical role in phishing detection. Harrison, Vishwanath, Ng, and Rao (2015) found that information that alludes to social presence fosters heuristic decision making and increases susceptibility to phishing. The authors manipulated social presence with cues such as the university logo, versing security logo, and click-to-chat icons.…”
Section: Physical Attributes Of Messages In Susceptibility To Phishingmentioning
confidence: 99%
“…They found that attention to visceral triggers and phishing detection indicators and to users' phishing knowledge played a critical role in phishing detection. Harrison, Vishwanath, Ng, and Rao (2015) found that information that alludes to social presence fosters heuristic decision making and increases susceptibility to phishing. The authors manipulated social presence with cues such as the university logo, versing security logo, and click-to-chat icons.…”
Section: Physical Attributes Of Messages In Susceptibility To Phishingmentioning
confidence: 99%
“…Harrison et al [87] studied how perceptions of social presence in a phishing attack influence the victimization rate. In their experiment, their participants were subject to a simulated phishing attack in which the amount of social presence in the email used was varied.…”
Section: Surveymentioning
confidence: 99%
“…Social presence is a concept defining the subjective and psychological experience of how information richness influences the persuasive effects of email. Harrison, et al [18] constructed an experiment to examine the amount of social presence in email and its relation to phishing victimization. The information richness that they deploy shows how sophistications (i.e.…”
Section: Trust Victimization and Phishingmentioning
confidence: 99%